The Immigrant War : A Global Movement Against Discrimination and Exploitation - Longhi, Vittorio, 1972- (Book collections on Project MUSE., 2013)
In this original, accessible book, Vittorio Longhi, a journalist who specializes in international labor matters, describes an emerging phenomenon of social conflict, in which migrants, are not conceived as passive victims of exploitation. Instead they are portrayed as conscious, vital social actors who are determined to organize and claim better rights. With a global perspective, The Immigrant War highlights the 'struggle for human rights, citizenship and equality'. In the context of a policy vacuum within the international community toward immigration. He demonstrates how these emerging conflicts can break the chain of exploitation and contribute to rethinking failing migration policiesand and the role of migrants in contemporary societies.